Predicting the Prognosis of Esophageal Adenocarcinoma by a Pyroptosis-Related Gene Signature - Zeng, Ruijie; Huang, Shujie; Qiu, Xinqi; Zhuo, Zewei; Wu, Huihuan; Jiang, Lei; Sha, Weihong; Chen, Hao (Frontiers in Pharmacology, 2021)
Esophageal adenocarcinoma (EAC) is a highly malignant type of digestive tract cancers with a poor prognosis despite therapeutic advances. Pyroptosis is an inflammatory form of programmed cell death, whereas the role of pyroptosis in EAC remains largely unknown. Herein, we identified a pyroptosis-related five-gene signature that was significantly correlated with the survival of EAC patients in The Cancer Genome Atlas (TCGA) cohort and an independent validation dataset. In addition, a nomogram based on the signature was constructed with novel prognostic values. Moreover, the downregulation of GSDMB within the signature is notably correlated with enhanced DNA methylation. The pyroptosis-related signature might be related to the immune response and regulation of the tumor microenvironment. Several inhibitors including GDC-0879 and PD-0325901 are promising to reverse the altered differentially expressed genes in the high-risk patients. Our findings provide insights into the involvement of pyroptosis in EAC progression, and is promising in the risk assessment as well as the prognosis for EAC patients in clinical practice.